2017
DOI: 10.1515/enr-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic regulation of the expression of genes encoded estrogen related proteins in U87 glioma cells: eff ect of IRE1 inhibition

Abstract: Objective. Th e aim of the present study was to examine the eff ect of inhibition of endoplasmic reticulum stress signaling, mediated by IRE1 (inositol requiring enzyme 1), which is a central mediator of the unfolded protein response on the expression of genes encoded estrogen related proteins (NRIP1/RIP140, TRIM16/EBBP, ESRRA/NR3B1, FAM162A/E2IG5, PGRMC2/PMBP, and SLC39A6/LIV-1) and their hypoxic regulation in U87 glioma cells for evaluation of their possible signifi cance in the control of glioma cells proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…The estrogen receptor antagonist, fulvestrant, was demonstrated to downregulate the IRE1/XBP1 signaling pathway in prolactinoma cells [45]. Conversely, Minchenko et al recently demonstrated that IRE1 inhibition modulates the expression of genes encoding estrogen related proteins in glioma cells [46]. Recent data supports a role for IRE1/XBP1 in glioblastoma development and progression and as such a promising therapeutic target [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen receptor antagonist, fulvestrant, was demonstrated to downregulate the IRE1/XBP1 signaling pathway in prolactinoma cells [45]. Conversely, Minchenko et al recently demonstrated that IRE1 inhibition modulates the expression of genes encoding estrogen related proteins in glioma cells [46]. Recent data supports a role for IRE1/XBP1 in glioblastoma development and progression and as such a promising therapeutic target [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no significant differences in the copy number of some important chromosome fragments like 1p and 19q between two groups, some amplified genes in high IFI30 level like NRIP1 and SSBP2 might participate in the promotion of GBM malignant progression. 16,17 High IFI30 Expression Conferred Chemotherapy Resistance in GBM…”
Section: High Ifi30 Expression-specific Somatic Mutations and Copy Numentioning
confidence: 99%
“…Еще одним важным фактором, способным регулировать экспрессию эстрогензависимых генов, к которым относят фактор TRIM16, является гипоксия. Показано увеличение его экспрессии в условиях гипоксии на клетках глиомы U87 [19], что считается значимым этапом в развитии опухолей.…”
Section: рис 1 значение Trim16 в развитии злокачественных новообразunclassified